Interpretasi Makna Waka Berunsur Kata Naniwa dalam Hyakunin Isshu: Kajian Semiotik - Sulthon Hernanda, Muhammad; Novitasari, Raden (Universitas Diponegoro, 2026)
This article took the field of semiotic research and focuses on interpretation of meanings of three Japanese poems/waka (和歌), that include the word ‘Naniwa’ (難波) from the famous Japanese poetry compilation, named Hyakunin Isshu (百人一首). The research conformed Michael Riffaterre's theory of semiotic readings, with procedure of: (1) heuristic reading, (2) hermeneutic reading, (3) matrix, model, variant, and (4) hypogram. This research used qualitative descriptive method, a research method that describes and illustrates linguistic phenomena. Heuristic reading produced referential meanings, while hermeneutic reading produced persuative meanings and indirect expressions due to the use of kakekotoba (掛詞), a pivotal vocabulary that is usually written only using hiragana letters, however its meaning refers to more than one vocabulary. The matrix on the 19th waka is